[Is there a solution to the drought? Recurrent water crises and the role of groundwater] - Sergio Rusi; Luca Alberti; Stefania Da Pelo; Giovanna De Filippis; Diego Di Curzio; Giovanni Forte; Manuela Lasagna; Marco Petitta; Vincenzo Piscopo; Elisabetta Preziosi; Marco Rotiroti; Glenda Taddia; et al. (Acque Sotterranee, 2022)
Not available